2014
DOI: 10.1186/s13014-014-0235-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of constant dose rate VMAT in the treatment of nasopharyngeal cancer patients

Abstract: PurposeTo investigate the feasibility of constant dose rate volumetric modulated arc therapy (CDR-VMAT) in the treatment of nasopharyngeal cancer (NPC) patients and to introduce rotational arc radiotherapy for linacs incapable of dose rate variation.Materials and methodsTwelve NPC patients with various stages treated previously using variable dose rate (VDR) VMAT were enrolled in this study. CDR-VMAT, VDR-VMAT and mutlicriteria optimization (MCO) VMAT plans were generated for each patient on RayStation treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Two investigated its role in the pelvic area 13,14 and one in nasopharyngeal cancer. 15 Comparing observations by Yu et al 15 with the present series is difficult because the former focused only on the nasopharyngeal area, while our series only included patients with oropharyngeal, hypopharyngeal and laryngeal cancer. Consequently, in the study by Yu et al, 15 some OARs such as the brainstem and parotids were closer to the PTV than in the present investigation so that maximum and mean doses were higher.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Two investigated its role in the pelvic area 13,14 and one in nasopharyngeal cancer. 15 Comparing observations by Yu et al 15 with the present series is difficult because the former focused only on the nasopharyngeal area, while our series only included patients with oropharyngeal, hypopharyngeal and laryngeal cancer. Consequently, in the study by Yu et al, 15 some OARs such as the brainstem and parotids were closer to the PTV than in the present investigation so that maximum and mean doses were higher.…”
Section: Discussionmentioning
confidence: 73%
“…Present results support using CDR-VMAT for head and neck radiotherapy as it emerged as a valid option when a dedicated linear accelerator is not available for VMAT therapy with variable dose-rates and gantry velocities. To date, few studies have focused on CDR-VMAT in treatment planning [11][12][13][14][15] with only three assessing the implications of using it in clinical practice. Two investigated its role in the pelvic area 13,14 and one in nasopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported for nasopharyngeal cancer, in which 12 previously treated patients were used for comparison between VDR, MCO, and CDR of 400 MU/min, results of this study showed no significant dosimetric differences between MCO, CDR and VDR plans. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that VDR VMAT is superior than CDR in terms of delivery time and number of MUs,[ 15 21 22 ] yet with significantly lower delivery time than IMRT. [ 11 ] This study demonstrated consistent increase of MUs as the constant dose rate increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation